2015
DOI: 10.1039/c5sc00685f
|View full text |Cite
|
Sign up to set email alerts
|

Water diffusion in atmospherically relevant α-pinene secondary organic material

Abstract: We report the first direct measurements of water diffusion coefficients in secondary organic aerosol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
190
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(197 citation statements)
references
References 71 publications
7
190
0
Order By: Relevance
“…Circles with a centered dot indicate that the data point is below the glass transition temperature. Water diffusivities in an α-pinene SOM of unknown O : C ratio reported recently by Price et al (2015) At lower temperatures we find that the water diffusivity of 3-MBTCA, levoglucosan and raffinose behaves similarly to that of the SOA extract (within ± 1 order of magnitude as indicated by the gray shaded area). Sucrose and shikimic acid, however, have a significantly stronger temperature dependence leading to differences in D w (T , 0) of about ten orders of magnitude at temperatures typical for the upper troposphere.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Circles with a centered dot indicate that the data point is below the glass transition temperature. Water diffusivities in an α-pinene SOM of unknown O : C ratio reported recently by Price et al (2015) At lower temperatures we find that the water diffusivity of 3-MBTCA, levoglucosan and raffinose behaves similarly to that of the SOA extract (within ± 1 order of magnitude as indicated by the gray shaded area). Sucrose and shikimic acid, however, have a significantly stronger temperature dependence leading to differences in D w (T , 0) of about ten orders of magnitude at temperatures typical for the upper troposphere.…”
Section: Resultssupporting
confidence: 72%
“…Further, it has been shown that chemical and physical processes occurring in the interior of the particle and at the gas/condensate interface are influenced by the viscous state in which condensed-phase diffusion is expected to slow down considerably (Debenedetti, 1996;Booth et al, 2014;Berkemeier et al, 2014). A much reduced water diffusivity slows down the growth of droplets compared with that predicted by equilibrium thermodynamics, but its significance for the ability of the droplets to act as ice nuclei or provide a medium for multi-phase chemistry is still poorly quantified (Murray et al, 2010;Shiraiwa et al, 2011;Koop et al, 2011;Price et al, 2015). This is mainly because viscosity, bounce factors and glass transition temperatures only provide indirect evidence for kinetic limitations of water diffusivity, whereas diffusion coefficients in the amorphous state span many orders of magnitude.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An aerosol's viscous state also has direct implications on the particle morphology, phase behaviour, optical properties, aging processes and lifetime. At the same time, only few direct measurement methods are available for monitoring such properties 1, [6][7][8][9][10][11][12][13][14][15][16] . Recently, we have demonstrated that viscosity of model organic aerosols, such as oleic acid droplets, and secondary organic aerosols (SOA) produced from the oxidation of myrcene or -pinene can be measured and imaged in a spatially and time-resolved manner using Fluorescence Lifetime Imaging Microscopy (FLIM) of molecular rotors 17 .…”
Section: Introductionmentioning
confidence: 99%
“…15 The change in diffusivity of small guest molecules is expected to be much smaller, for example, from 10 À5 cm 2 s À1 to about 10 À10 to 10 À12 cm 2 s À1 for water at room temperature. 9,16 These changes in diffusion coefficients have important implications for mass transport based processes such as gas-particle partitioning. 17 A study by Abramson et al on evaporation from a-pinene-derived SOA shows that pyrene present during SOA formation gets trapped and despite its relatively high volatility evaporates only slowly due to slow diffusion within the bulk.…”
mentioning
confidence: 99%